Experimental multiplexing of encrypted movies using a JTC architecture - Barrera, John Fredy (2012)
We present the first experimental technique to encrypt a movie under a joint transform correlator architecture. We also extend the method to multiplex several movies in a single package. We use a Mach-Zehnder interferometer to encrypt experimentally each movie. One arm of the interferometer is the joint transform correlator and the other arm is the reference wave. We include the complete description of the procedure along with experimental results supporting the proposal.